Analyze the Students’ Conceptual Understanding of Elasticity and Hooke’s Law Using the Rasch Model - Rafiah, Jihan Ariqatur; Miyaqi, Iqlides Ahmad (Impulse: Journal of Research and Innovation in Physics Education, 2025)
This study investigates students’ conceptual understanding of Elasticity and Hooke’s Law by employing the Rasch measurement model. Conceptual understanding in physics is essential for enabling learners to apply principles across contexts and develop critical thinking skills. The 20 items multiple-choice test was developed and validated to assess mastery of elasticity-related concepts. The approach in this study was quantitative that conducted in Yogyakarta, Indonesia, involving 56 senior high students who had completed lessons on the relevant topic. The Rasch model was applied using the Ministeps software to analyze item difficulty and student ability. The Wright map and fit statistics indicated that most students had low to moderate levels.